Astroglial mGlu3 receptors promote alpha-secretase-mediated amyloid precursor protein cleavage - Durand, Daniela Elizabeth (2013)
Amyloid precursor protein (APP) shedding yields the Alzheimer´s disease (AD)-related peptide amyloid B (AB) through beta- and gamma-secretase cleavage. Alternatively, alpha-secretase cleavage generates a soluble and neuroprotective fragment (sAPPalpha) while precludes the production of AB. Although metabotropic glutamate (mGlu) receptors were associated with induction of sAPPalpha production in astrocytes, there was no further evidence regarding the specific subtype receptor or the mechanisms involved in this action. In the present study, we used the dual mGlu2/3 receptor agonist LY379268, which in pure astrocyte cultures selectively activates mGlu3 receptor subtype since mGlu2 receptor subtype is not expressed by these cells. We showed that LY379268 incremented sAPPalpha release from cultured astrocytes by inducing alpha-secretases expression, whereas it decreased beta-secretase levels. LY379268-induced increase of PPAR-gamma levels could be involved in the effect of the agonist on sAPPalpha release. Using the PDAPP-J20 murine model of AD we described a strong reduction in mGlu2/3 receptor expression in the hippocampus of 5- and 14-month-old transgenic mice compared to control littermates. Moreover, mGlu3 receptor expression is also decreased specifically in hippocampal astrocytes of these transgenic animals as a function of age. Therefore, diminished levels of hippocampal mGlu3 receptors might have implications in the development of the disease in these transgenic mice considering the anti-amyloidogenic action of mGlu3 receptors in astrocytes.